Financial Distress Prediction of Mining Companies Listed In Indonesian Stock Exchange: An Analysis Using Altman Z-Score Model - Saden, Novian Seno; Prihatiningtias, Yeney Widya (Jurnal Ilmiah Mahasiswa FEB, 2015)
Financial distress condition can have a severe consequences such as a degradation in companiesâ€™ performances and the worst scenario is bankruptcy to the companies who are experiencing it. Therefore it is imperative for the companies to investigate the causes that may lead to a corporate bankruptcy and take a necessary action in order to prevent such situation. Thus, this study investigate the financial distress signal among 18 mining companies listed in Indonesian stock exchange which are divided into three subsectors of metallic mineral, coal, and oil & gas mining over the period of four years (2011-2014). This research assess the financial distress determinant measured by Altman Z-score model. Furthermore, this study also examine which of the three subsectors have a better Z-score ratio using Kruskal-Wallis statistical model. The result of the study shows that metallic mineral mining have the highest Z-score ratio compared to the coal sector and oil & gas sector, while the lowest Z-score are experienced by oil & gas sector and coal mining sector being the second highest. The result also shows that there were mining companies who experienced financial distress through the four years period, in which all of the three subsectors had experienced an increase number of financial distress companies year by year. Keywords: Financial Distress, Bankruptcy, Altman Z-Score Model, Mining Companies, Metallic Mineral, Coal, Oil & Gas. Â